Ultra low power bioelectronics : fundamentals, biomedical applications, and bio-inspired systems - Sarpeshkar, Rahul, 1968- (Cambridge, UK ; New York : Cambridge University Press, 2010)
"This book provides, for the first time, a broad and deep treatment of the fields of both ultra low power electronics and bioelectronics. It discusses fundamental principles and circuits for ultra low power electronic design and their applications in biomedical systems. It also discusses how ultra energy efficient cellular and neural systems in biology can inspire revolutionary low power architectures in mixed-signal and RF electronics. The book presents a unique, unifying view of ultra low power analog and digital electronics and emphasizes the use of the ultra energy efficient subthreshold regime of transistor operation in both. Chapters on batteries, energy harvesting, and the future of energy provide an understanding of fundamental relationships between energy use and energy generation at small scales and at large scales. A wealth of insights and examples from brain implants, cochlear implants, bio-molecular sensing, cardiac devices, and bio-inspired systems make the book useful and engaging for students and practising engineers"--Provided by publisher.
Machine generated contents note: 1. The big picture; 2. Feedback systems: fundamentals, benefits, and root-locus analysis; 3. MOS device physics: general treatment; 4. MOS device physics: practical treatment; 5. MOS device physics: small-signal operation; 6. Deep-sub-micron effects in MOS transistors; 7. Noise in devices; 8. Noise in electrical and non-electrical circuits; 9. Feedback systems: the Nyquist criterion, compensation techniques, positive feedback, and small-signal circuits; 10. Return-ratio analysis; 11. Low-power transimpedance amplifiers and photoreceptors; 12. Low-power transconductance amplifiers, first-order systems, and scaling laws for power in analog circuits; 13. Low-power filters and resonators; 14. Low-power current-mode circuits; 15. Ultra-low-power and neuron-inspired analog-to-digital conversion for biomedical systems; 16. Wireless inductive power links for medical implants; 17. Energy-harvesting RF antenna power links; 18. Low-power RF telemetry in biomedical implants; 19. Ultra-low-power implantable medical electronics; 20. Ultra-low-power non-invasive medical electronics; 21. Principles for ultra-low-power digital design; 22. Principles for ultra-low-power analog and mixed-signal design; 23. Neuromorphic electronics; 24. Cytomorphic electronics: cell-inspired electronics for large-scale systems and synthetic biology; 25. Batteries and electrochemistry; 26. Energy harvesting and the future of energy.
Includes bibliographical references and index.
Keywords: Low voltage systems; Biomimicry; Bioelectronics; Bionics; Medical electronics